Orality and subalternity: The creation of the Earth and other Stories of the good Sibú and the bribris by Adela Ferreto - Hernández Gómez, Abelardo (2020)
This paper is a reflection on the role of one of the existing indigenous cultures in the Costa Rican territory, namely the Bri Bri culture within written-westernized literature. The objective is to highlight the position of indigenous cultural traditions within the literary institution. For such purpose, the text of Adela Ferreto La creación de la Tierra y otras Historias del buen Sibú y de los bribris (The Creation of the Earth and other Stories by the good Sibu and Bribri people, whose narratives are based on indigenous orality, is considered